Use of Gis for Spatial Mapping of Soil Fertility in Dhanusha, Nepal - Santosh kumar Yadav; Karuna Kafle; Abichal Poudel; Rashil Gelal; Bhushan Adhikari (Hasanuddin University, 2022)
Soil fertility evaluation is an important aspect in the context of sustainable agricultural production of an area. This study was carried out to find the soil fertility status of the Dhanushadham Municipality, Dhanusha, Nepal located at 26°52’N, 86o02’E using GPS and GIS. A total of 61 soil samples were collected based on land use, slope, and aspects with the use of Google Earth Pro (GEP) and ArcGIS. The soil was analyzed for its texture, soil pH, total nitrogen, available phosphorous, and potassium. The majority of the study area (36.35%) has loam soils followed by (28.17%) sandy loam soil. The soil pH was strongly acidic to nearly neutral with pH values ranging from 5.2 to 7.5. The Soil organic matter (SOM) varied from 1.14% to 1.83% with a mean value of 1.52% and was medium in most of the soil. The mean total Nitrogen, available phosphorus, and available potassium were 0.08 %, 120.96 kg/ha, and 146.13 kg/ha respectively. The total nitrogen was found to be medium in content, Phosphorus is high in content and potassium is low in content in the study area. To maintain the nutrient status of soil, use of organic manure, reduced use of chemical fertilizers, and different soil management practices should be adopted in this area. The study can conclude that GPS and GIS based soil fertility mapping helps farmers, scientists, planners, researchers, and students in providing soil test based fertilizer recommendation for sustainable soil management as well as developing future research strategies in the farm.